Design Proposal for a Rotating Children’s House Using Anthropometric and Hand Tools Approach - Alda Bella Oseasky; Demas Emirbuwono Basuki; Nabila Aulia Azizah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Early childhood, especially under the age of 5, is a critical period for the development of intelligence, with research showing that at the age of 4, a child's intelligence capacity has reached 50%, increasing to 80% at the age of 8. The focus of this study is the redesign of playground equipment, especially children's playhouses, using an anthropometric approach to ensure safety and comfort for children. This study involved 30 children aged 3-5 years with body dimension measurements that support ergonomic design. Normality tests showed the right distribution data using the 95th and 5th percentiles of body dimensions, ensuring a safe and comfortable design. The test results showed this design is more suitable for children living in the city because it showed a 15% increase in safety and 20% comfort. Keywords: Anthropometry, Ergonomic Design, Child growth pattern, Body dimension